A interação entre sistemas de informação e o trabalho no setor bancário no Brasil: uma análise estruturalista - Rodrigues, Elaine Maria Tavares (2008)
This thesis had the objective of understanding in which conditions the process of interaction between the work and three information systems (IS) used in two banks in Brazil is developed. I studied how users, in work practices, reconstruct the systems and how the work is modified by new systems implementations. Appling methodological procedures based on the structuralism method, the research aimed to reveal the structure behind practices adopted by agents, related to the systems and to the work. Data were collected through semistructured interviews, with 46 IT managers and users. In addition to the interviews, it was also used observation and analysis of documents related to the systems. The data analysis was initiated by the diagnosis and study of 11 practices that allowed me to identify which ones were more relevant to the interaction between agents and technological devices, related to reconstructions in IS and changes in work. I identified, in the field research, a structure of operational arrangement, which assures the interaction between agents and IS. This arrangement is a graticule of practices overlaps, a network of relationships. The practice, by itself, does not assure the interaction between the system and work. This interaction is guaranteed by the practices composition. Interpreting this arrangement, I identified the structure behind the interaction of IS and work. The analysis of practices explanations revealed a set of elements of power and resistance, confluence of individuals and organizational objectives, and conformism and conformity of the agents to what was established by the organization. The analysis of these elements allowed me to obtain the thesis defended by this research: the interaction between the information systems and the work is defined by a structure of reciprocal conversion. This conversion consists on the systems humanization and by the incorporation of technical aspects to the work. The continued adjustment, presented between IS and work, allows technologies to be more appropriate to the context and people to become more prepared to deal with technology. The structure of reciprocal conversion has the shape of an oroborus, a serpent that swallows or vomits its own tail and symbolizes something that regenerates itself, a reconstruction. Like an oroborus, the structure of reciprocal conversion is a self-reconstruction.